Erik Satie’s Socrate (1918), Myths of Marsyas, and un style dépouillé - Dorf, Samuel N. (Current Musicology, 2014)
It is almost easier to say what Erik Satie’s Socrate is not rather than what it is. It has proved enigmatic since its première, when the audience giggled at its conclusion, confused by the strange sincerity of the work, especially since it was written by a composer known for his humorous piano pieces (Harding 1975, 183). Scholars have defined Socrate’s clear, unadorned musical lines as modernist, abstract, and even quasi–socialist and minimalist (see Danuser 2004, 261–62; Shattuck 1968, 168; Fulcher 2005, 146–51; and Wilson 2007, 215–16). The work also defies traditional categorizations of genre: Satie designated Socrate not as an oratorio, a symphony, or an opera, but as a drame symphonique, scored for chamber orchestra and four soprani. Satie envisioned the work as incidental music for the reading of Plato. The soprani sing selections in French from Plato’s dialogues on the life of Socrates in a detached style, as if reading. Socrate eschews the grand theatricality of the opera stage in favor of the intimacy of the salon. Socrate resists spectacle.